Pioneers in surgical gastroenterology - Gillison, Walford; Buchwald, Henry (Tfm Pub., 2007)
This book is both a lively introduction and a guidebook to those pioneers, most of them surgeons, who attempted to help their patients by extending the boundaries of their own knowledge and experience. In the 16 chapters of the book, an international group of authors have provided something of value to all those with an interest in surgical gastroenterology. Medical students and young trainees will come to understand the principles behind modern gastrointestinal surgery.